2017
DOI: 10.1016/j.cell.2017.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Granzyme B Disrupts Central Metabolism and Protein Synthesis in Bacteria to Promote an Immune Cell Death Program

Abstract: SUMMARY Human cytotoxic lymphocytes kill intracellular microbes. The cytotoxic granule granzyme proteases released by cytotoxic lymphocytes trigger oxidative bacterial death by disrupting electron transport, generating superoxide anion and inactivating bacterial oxidative defenses. However, they also cause non-oxidative cell death, since anaerobic bacteria are also killed. Here we use differential proteomics to identify granzyme B substrates in three unrelated bacteria, Escherichia coli, Listeria monocytogenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 46 publications
1
51
0
Order By: Relevance
“…73 Additional work has shown that granzyme B cleaves a number of essential proteins in both gram positive and negative bacteria that are responsible for protein synthesis and metabolism. 83 Inhibition and knockout of granzymes in murine iNKT cells abrogated killing of Borrelia burgdoferi, inhibition of perforin also blocked killing but to a lesser extent, suggesting both effector molecules played a role in killing. 84 Different combinations of effector molecules have an additive effect, each exerting a separate antimicrobial effect, through independent mechanisms, leading to greater antimicrobial activity.…”
Section: Effector Moleculesmentioning
confidence: 98%
See 1 more Smart Citation
“…73 Additional work has shown that granzyme B cleaves a number of essential proteins in both gram positive and negative bacteria that are responsible for protein synthesis and metabolism. 83 Inhibition and knockout of granzymes in murine iNKT cells abrogated killing of Borrelia burgdoferi, inhibition of perforin also blocked killing but to a lesser extent, suggesting both effector molecules played a role in killing. 84 Different combinations of effector molecules have an additive effect, each exerting a separate antimicrobial effect, through independent mechanisms, leading to greater antimicrobial activity.…”
Section: Effector Moleculesmentioning
confidence: 98%
“…Granzymes have been previously shown to enter bacteria via granulysin‐mediated pore formation, and cleave complex I of the electron transport chain in aerobic bacteria to generate superoxide anions that can bring damage to the cell and lead to death . Additional work has shown that granzyme B cleaves a number of essential proteins in both gram positive and negative bacteria that are responsible for protein synthesis and metabolism . Inhibition and knockout of granzymes in murine iNKT cells abrogated killing of Borrelia burgdoferi , inhibition of perforin also blocked killing but to a lesser extent, suggesting both effector molecules played a role in killing …”
Section: Effector Moleculesmentioning
confidence: 99%
“…A crucial line of evidence for the claim that gd T cells restrict parasite growth in a Gzm-dependent manner is the identification of plasmodial proteins that are targeted and efficiently destroyed by the effector immune proteases. Recent studies revealed that oxidative defense enzymes (18,19), the Clp protease system, and the virulence machinery (40) are predominantly targeted in microbial pathogens by the Gzms. In this study, we found that ClpR, a proteolytic subunit of the Clp system in P. falciparum, the major antioxidant enzyme 1-cys peroxiredoxin (1-cys Pxn), as well as the extracellular domain of one of the rifins, essential plasmodial virulence mediators, were efficiently cleaved by GzmB.…”
Section: Gnly-delivered Gzmb Reduces Atp Production As Well As Reinvamentioning
confidence: 99%
“…GrzB is produced by cytotoxic cells like NK cells (19) and CD8 + T cells (20). In various inflammatory diseases GrzB spills over from direct contact between cytotoxic cells and target cells and can be measured in the circulation, which might represent a surrogate marker of immune activation during infections (21) or autoimmune disease (22).…”
Section: Discussionmentioning
confidence: 99%